Managerial and Entrepreneurial Decision Making Emerging Issues - Cristofaro, Matteo; Sousa, Maria José; Sánchez-García, José Carlos; Larsson, Aron (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Since the conceptualization of bounded rationality, management scholars started investigating how people-managers and entrepreneurs-really make decisions within (and for) organizations. The aim of this eBook is to deeply investigate trends that have flourished within this pivotal research area in conceptual and/or empirical terms, trying to provide new insights on how managers and entrepreneurs make decisions within and for organizations. In this vein, readers that approach this eBook will be taken by hand and accompanied to the discovery of how the mind of decision makers is at the basis of organizational developments or failures. In this regard, published contributions in this eBook underline how executives and entrepreneurs must be ecologically rational, thus be aware of the negative and positive effects that biases can have depending on the context and use them at their advantage. Managerial and entrepreneurial decision-making are phenomena that cannot be detached from the environment in which executives and entrepreneurs are embedded, claiming to establish new approaches to research that looks at decision-making as an individual/group/organization-environment dialectical and multi-level phenomenon.